Heterobimetallic Complexes for Theranostic Applications - Fernández‐Moreira, Vanesa; Gimeno, M. Concepción (Chemistry : a European journal, 2018)
The design of more efficient anticancer drugs requires a deeper understanding of their biodistribution and mechanism of action. Cell imaging agents could help to gain insight into biological processes and, consequently, the best strategy for attaining suitable scaffolds in which both biological and imaging properties are maximized. A new concept arises in this field that is the combination of two metal fragments as collaborative partners to provide the precise emissive properties to visualize the cell as well as the optimum cytotoxic activity to build more potent and selective chemotherapeutic agents. The design of more efficient drugs requires a deeper understanding of their biological distribution and mechanism of action. A smart approach would be the combination of two well‐known metallic fragments, that is, a luminescent and a bioactive fragment, able to generate a synergy between their intrinsic properties. Thus, it will be feasible to use non‐invasive techniques such as fluorescence microscopy to reveal key information for future advances in medicine.